PENGAWASAN NARAPIDANA KELAS II B DI RUMAH TAHANAN NEGARA KOTA DUMAI - Nabila, Tasa; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Supervision of class II B Prisoners in Dumai City State Detention Center is based on Regulation of the minister of Law on Regulation of the minister of Law and Human Rights Number 6 of 2013 about Orders for Prisoners. Carrying out security and order is an absolute teaching for the implementation of coaching programs and security aspects in State Detention Centers as indicators of the success of the detention center but its supervision has not run optimally, this can be seen from the lack of strict supervision of prisoners resulting in cases in the remand center because they see the current conditions that have exceeded the capacity and number of officers who do not meet the standards. This study aims to determine the supervision of class II B prisoners in the Dumai City State Detention Center and to find out what factors are obstacles to the supervision of these prisoners. The concept of the theory used the Supervision theory in the Manullang book, namely: (1) Establish a measuring device (Standar), (2) conduct an assessment, (3) carry out corrective actions. This study used descriptive qualitative method. In data collection researchers used observation, interview and documentation techniques. The results of this study indicate that the supervision of prisoners in the Dumai City Detention Center still has many defeciencies and is still not running optimally. In this study, its known that the factors that inhibit the supervision of prisoners in class II B in the Dumai City Prison include the lack of correctional staff, facilities and infrastructure, training in human resources.Keywords: Supervision, State Prison, Exceed Capacity